2020
DOI: 10.1093/mnras/staa3250
|View full text |Cite
|
Sign up to set email alerts
|

The S2 Stream: the shreds of a primitive dwarf galaxy.*

Abstract: The S2 stream is a kinematically cold stream that is plunging downwards through the Galactic disc. It may be part of a hotter and more diffuse structure called the Helmi stream. We present a multi-instrument chemical analysis of the stars in the metal-poor S2 stream using both high- and low-resolution spectroscopy, complemented with a re-analysis of the archival data to give a total sample of 62 S2 members. Our high-resolution program provides α-elements (C, Mg, Si, Ca and Ti), iron-peak elements (V, Cr, Mn, F… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
27
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 234 publications
(274 reference statements)
5
27
2
Order By: Relevance
“…It has also been associated with 4 RPE stars. This could be another strong indication that, in the very low-metallicity regime, the progenitor of the HStr experienced enrichment in neutron-capture elements pre-dominantly via the r-process, in accord with other recent results from chemical-abundance analyses (Roederer et al 2010;Aguado et al 2020).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…It has also been associated with 4 RPE stars. This could be another strong indication that, in the very low-metallicity regime, the progenitor of the HStr experienced enrichment in neutron-capture elements pre-dominantly via the r-process, in accord with other recent results from chemical-abundance analyses (Roederer et al 2010;Aguado et al 2020).…”
Section: Discussionsupporting
confidence: 89%
“…Three of these stars have very similar [Eu/Fe] ratios ([Eu/Fe] ≈ +0.40; r-I), and the other is more enriched in r-process elements ([Eu/Fe] = +1.07; r-II). The excess of RPE stars in this substructure is also consistent with recent spectroscopic efforts (Roederer et al 2010;Aguado et al 2020). In both works, the authors argued that the enrichment in neutron-capture elements of the member stars of the HStr was dominated by the r-process, based on their [Sr/Ba] patterns at the VMP end.…”
Section: Connections To Rpe Starssupporting
confidence: 84%
See 1 more Smart Citation
“…[Fe/H] −1.4; its average metallicity is [Fe/H] = −2.0, consistent with Aguado et al (2021) and others in the literature (e.g., Myeong et al 2018a,b). Additionally, the [Fe/H] dispersion of ≈ 0.5 dex found for CDTG-15 leads to a CDF value of 0.71 (commensurate with random draws from the full RPE Sample), consistent with its progenitor being a dwarf galaxy with extended star formation (see Koppelman et al 2019b).…”
Section: Statistical Significance Of the Resultssupporting
confidence: 89%
“…Limberg et al (2020) has also suggested a connection between this stream and RPE stars based on their dynamics. It is striking that spectroscopic studies of this structure had already claimed that its stars were enriched in neutron-capture elements, primarily via the r-process, based on the close conformity among the abundances of Ba and many elements in the rare-earth domain to the scaled-solar r-process pattern (Roederer et al 2010) or their [Sr/Ba] profiles (Aguado et al 2021).…”
Section: Statistical Significance Of the Resultsmentioning
confidence: 99%